2021
DOI: 10.1091/mbc.e20-10-0664
|View full text |Cite
|
Sign up to set email alerts
|

Arf1 orchestrates Rab GTPase conversion at the trans-Golgi network

Abstract: Rab family GTPases are key organizers of membrane trafficking and function as markers of organelle identity. Accordingly, Rab GTPases often occupy specific membrane domains and mechanisms exist to prevent the inappropriate mixing of distinct Rab domains. The yeast Golgi complex can be divided into two broad Rab domains: Ypt1 (Rab1) and Ypt6 (Rab6) are present at the early/medial Golgi and sharply transition to Ypt31/32 (Rab11) at the late Golgi/ trans-Golgi network (TGN). This Rab conversion has been attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Similarly, the localization of apical cargo protein NHX-2 (Na+/H+ exchanger) and basolateral recycling regulator LET-413/Erbin were affected ( Figure 1C-C′ ). Previous studies suggested that SMAP2 could act as an Arf1GAP (Arf1 GTPase-activating protein) and regulate the formation of the clathrin coat on the trans-Golgi network (TGN) ( Thomas et al, 2021 ), leading us to examine the distribution of GFP-ARF-1.2. In smap-1(ycxEx1639) cells, GFP-ARF-1.2 accumulated in punctate structures ( Supplementary Figure S3A-A′ ), suggesting that SMAP-1 acts as a GAP of ARF-1.2 in intestinal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the localization of apical cargo protein NHX-2 (Na+/H+ exchanger) and basolateral recycling regulator LET-413/Erbin were affected ( Figure 1C-C′ ). Previous studies suggested that SMAP2 could act as an Arf1GAP (Arf1 GTPase-activating protein) and regulate the formation of the clathrin coat on the trans-Golgi network (TGN) ( Thomas et al, 2021 ), leading us to examine the distribution of GFP-ARF-1.2. In smap-1(ycxEx1639) cells, GFP-ARF-1.2 accumulated in punctate structures ( Supplementary Figure S3A-A′ ), suggesting that SMAP-1 acts as a GAP of ARF-1.2 in intestinal cells.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the functionality of clathrin, in addition to clathrin-coated pits during endocytosis, clathrin-coated vesicles also bud from TGN. Arf1 triggers the assembly of the clathrin coat on TGN ( Thomas et al, 2021 ). A mechanistic study revealed that TGN-associated clathrin and AP-1 quickly exchange with free proteins in the cytoplasm, and AP-1 can exchange independently of clathrin ( Wu et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arf1 is also proposed to be the key driver of Rab distribution during Golgi maturation. It was shown that the level of both Ypt1 and Ypt6 decline at the late Golgi before Ypt31/32 reaches the highest activity, suggesting the existence of extra factors to initiate the recruitment of GAP proteins for Ypt1 and Ypt6 (namely the Gyp1 and Gyp6) (Thomas et al, 2021). Arf1 was proposed to be a potential regulator in that both GAPs accumulate right after the peak activation of Sec7 (Thomas et al, 2021).…”
Section: Crosstalk Of Arf Family Proteins Arf Gefs and Arf Gapsmentioning
confidence: 99%
“…It was shown that the level of both Ypt1 and Ypt6 decline at the late Golgi before Ypt31/32 reaches the highest activity, suggesting the existence of extra factors to initiate the recruitment of GAP proteins for Ypt1 and Ypt6 (namely the Gyp1 and Gyp6) (Thomas et al, 2021). Arf1 was proposed to be a potential regulator in that both GAPs accumulate right after the peak activation of Sec7 (Thomas et al, 2021). Indeed, Arf1 binds directly to Gyp1 both in vivo and in vitro, and Gyp1 and Gyp6 were severely mis-localized in Arf1 and TRAPPII mutant (Thomas et al, 2021).…”
Section: Crosstalk Of Arf Family Proteins Arf Gefs and Arf Gapsmentioning
confidence: 99%
“…Gyp1, another GAP for Ypt1, is located in the early Golgi [ 89 ]. Their location in membranes depends on Arf1 GTPase, which recruits Gyp1 inactivating Ypt1 [ 90 ]. This sequential gradient of activation/inactivation of GTPases is important for maintaining compartment identity, ensuring cisternae maturation, and guiding the secretory traffic [ 91 , 92 ].…”
Section: Rab1mentioning
confidence: 99%